Are we facing a cure in lung cancer?—KEYNOTE-001 insights - Cohen, Aharon Y.; Kian, Waleed; Roisman, Laila C.; Levitas, Dina; Peled, Nir; Dudnik, Yulia (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Pembrolizumab is a humanized monoclonal antibody that blocks the programmed death 1 receptor (PD-1) and has antitumor activity in advanced non-small-cell lung cancer (NSCLC). The phase 1 trial first published in 2015, included a total of 495 advanced NSCLC patients. The patients received pembrolizumab at a dose of either 2 or 10 mg per kilogram of body weight every 3 weeks or 10 mg per kilogram every 2 weeks with progression-free survival (PFS) of 3.7 months and median duration of response (DOR) of 12.5 months. Among all patients, the median overall survival (OS) was 12.0 months. In patients with a PD-L1 immunohistochemistry [tumor proportion score (TPS)] score of at least 50% the median PFS was 6.3 months and the response rate was 45.2%, thus, the median OS was not reached (1).